Dampak Model Pelatihan Partisipatif Berbasis Komunitas Belajar Terhadap Kinerja Guru SMAN 1 Gunungsindur - Rohimat, Japar; Kamil, Mustofa; Saripah, Iip (Jurnal Ilmiah Global Education, 2025)
This research investigates the influence of a participatory training model grounded in learning communities on the performance of teachers at SMAN 1 Gunungsindur. The approach prioritizes active teacher participation in collaborative learning, experience exchange, and the implementation of innovative instructional techniques. Utilizing a quasi-experimental design with a quantitative methodology, data collection was conducted through surveys, observations, and interviews, followed by analysis using t-tests and simple linear regression. Findings reveal that training based on learning communities significantly improves pedagogical competence, teaching enthusiasm, and classroom management efficiency. Additionally, it enhances teachers' capacity to produce scientific papers. Hypothesis testing demonstrates a substantial improvement in teacher performance post-training compared to pre-training (p < 0.05). Essential success determinants include a cooperative school environment and favorable educational policies. Nonetheless, constraints such as time limitations and a shortage of skilled facilitators present challenges. Consequently, this study advocates for the broader adoption of this training model to sustainably enhance education quality.